Effect of source in online video training for pre-harvest strategies for the control of E. Coli - Chapes, Joseph (Kansas State University, 2016)
Escherichia Coli (E. Coli) contamination has been a long-existing concern for those engaged in cattle production, often causing negative public health and economic consequences. The existence of pre-harvest practices that reduce E. coli contamination creates the opportunity to support human health by focusing on modifying behaviors in cattle production through educational communication. It is vital to consider how the communication can be modified to persuade the audience. This study examined the effects of different sources, such as a veterinarian or a cattle producer, presenting the educational message in a training video. An experimental design was used to examine how the information source used in a video relates to the source’s credibility, as well as testing concepts related to the theory of planned behavior. A link to a video and an online questionnaire were distributed to cattle producers through the weekly news e-mail distributed by several beef industry organizations. The data analysis of 106 complete questionnaires found that no matter how a presenter was described in a training video there was no difference in the perceived credibility of the presenter. Also, no matter how the source was identified there was no difference in the variables related to the theory of planned behavior and possible behavior adoption. In addition to these results, this study found that no matter how the source was labeled, higher perceived credibility correlated with more positive attitudes, perceived norms, perceived behavior control and reported intention to adopt the suggested behaviors. This pattern provides evidence for credibility’s relationship with possible behavior adoption, indicating that credibility of the source is an important consideration when message designers are constructing training videos.
Keywords: Source credibility; Theory of planned behavior; E. coli control; Cattle production; Online videos; Video training